Solving livestock feed problems can accelerate economic and social development in Ethiopia - Melaku, Mulugeta Tilahun; Mulatu, Kalkidan Ayele; Mwendia, Solomon Waweru; Notenbaert, An Maria Omer; Yedra Cubillos, Anny Isabella; Bekele, Regassa (2025)
The Alliance of Bioversity International and CIAT, in collaboration with Ethiopia’s Ministry of Agriculture (MoA), organized a training-of-trainers (ToT) workshop in Hawassa from August 8–10, 2025. The event was part of the CGIAR Scaling for Impact (S4I) Science Program, which aims to bridge the gap between research and extension systems by fostering collaboration, system integration, and collective action. The training focused on scaling up grass–legume forage technologies to improve mixed farming productivity and promote environmental sustainability.